Arguments in favour of compulsory treatment of opioid dependence - Zunyou Wu (Bulletin of the World Health Organization)
Twelve agencies of the United Nations, including the World Health Organization, have issued a joint statement that calls on Member States to replace the compulsory detention of people who use opioids in treatment centres with voluntary, evidence-informed and rights-based health and social services. The arguments in favour of this position fall into three broad categories: Compulsory treatment centres infringe on an individual's liberty, they put human beings at risk of harm, and evidence of their effectiveness against opioid dependence has not been generated. The United Nations statement underscores that although countries apply different criteria for sending individuals to compulsory treatment centres, detention often takes place without due process, legal safeguards or judicial review. This clearly violates internationally recognized human rights standards. Furthermore, people who are committed to these centres are often exposed to physical and sexual violence, forced labour and sub-standard living conditions. They are often denied health care, despite their heightened vulnerability to HIV infection and tuberculosis. Finally, there is no evidence, according to the statement, that these centres offer an environment that is conducive to recovery from opioid dependence or to the rehabilitation of commercial sex workers or of children who have suffered sexual exploitation, abuse or lack of care and protection. The author of this paper sets forth several arguments that counter the position taken by the United Nations and argues in favour of compulsory treatment within a broader harm reduction strategy aimed at protecting society as well as the individual concerned.